2021
DOI: 10.1093/biolre/ioab234
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-reprogrammed CHRM3 results in vascular dysfunction in the human umbilical vein following IVF-ET

Abstract: Assisted reproductive technology (ART) has been used globally among infertile couples. However, many epidemiological investigations have indicated that ART is associated with a range of long-term adverse health outcomes in offspring, including cardiovascular disease, obesity and increased plasma lipid levels. Until now, direct evidence has been limited regarding the pathological changes in vascular function in fetuses with ART. In this study, human umbilical cords were collected from healthy normal pregnancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…It has been reported to increase fasting blood glucose levels [8], blood pressure [8,9], adiposity, triglyceride levels [10], and vascular dysfunction [9,11,12] in IVF children. In our recent studies, we found that umbilical veins of IVF-ET offspring showed abnormal sensitivity to acetylcholine (ACh) or angiotensin II (AII)-mediated contraction, which could be caused by hypo/hypermethylation of the speci c receptors [13,14]. Our ndings strongly supported the idea that IVF-ET could directly lead to changes in fetal vessel functions, which might result in cardiovascular disorders in the long term.…”
supporting
confidence: 72%
“…It has been reported to increase fasting blood glucose levels [8], blood pressure [8,9], adiposity, triglyceride levels [10], and vascular dysfunction [9,11,12] in IVF children. In our recent studies, we found that umbilical veins of IVF-ET offspring showed abnormal sensitivity to acetylcholine (ACh) or angiotensin II (AII)-mediated contraction, which could be caused by hypo/hypermethylation of the speci c receptors [13,14]. Our ndings strongly supported the idea that IVF-ET could directly lead to changes in fetal vessel functions, which might result in cardiovascular disorders in the long term.…”
supporting
confidence: 72%
“…Recent studies reported that angiotensin II-mediated vasoconstrictions were greater in umbilical veins from pregnancy who received IVF-ET when comparing with the control [ 13 ]. But the contractile response to acetylcholine was lower in IVF-ET group [ 12 ]. However, previous vascular functional studies on HUV did not distinguish samples between fresh or frozen ET.…”
Section: Discussionmentioning
confidence: 99%
“…Due to lack of autonomic innervation, vessel tone of human umbilical vessels is mainly regulated by vasoactive substances released locally or carried by the blood stream, such as histamine [ 10 , 11 ]. Recent studies reported that IVF-ET could alter the constriction caused by angiotensin II and acetylcholine in the HUVs via abnormal DNA methylation [ 12 , 13 ]. However, there have been very limited data on the effects of frozen ET process on vascular functions in human.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…M3R is widely distributed in the human heart, has an inotropic effect, and plays vital roles in various cardiac functions, including the regulation of heart rate, mitigation of myocardial ischemic injury, facilitation of cell‐to‐cell communication, and prevention of atrial fibrillation 15,16 . In addition, M3R is expressed in the endothelial cell layer and smooth muscle cells of the vascular system, where it mediates vasodilation and vasoconstriction 17,18 . Moreover, M3R is involved in the regulation of BP.…”
Section: Introductionmentioning
confidence: 99%